Perbedaan Indeks Prestasi Kumulatif (IPK) Mahasiswa Pendidikan Akuntansi IKIP PGRI Madiun Berdasarkan Status Mahasiswa Kos Dan Tidak Kos - Ananda Rivia Ardianti; ElaKatarina Dwi Sari (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
This research aim to test difference of Cumulative Index Achievement of Student Education Of Accountancy of IKIP PGRI Madiun. Population in this research is semester student of VII Education Of Accountancy of IKIP PGRI Madiun. Amount of sampel is 100 student. Hypothesis in this research is tested with test of T-Test ( Different Test / test of T free sampel). Result of this research indicate that are not difference of Cumulative Index Achievement ( IPK) Student pursuant to student status board with and do not board with.